MICROPROPAGATION OF GRAPEVINE '420-A' ROOTSTOCK - DZAZIO, Pryscilla Menarin (Scientia Agraria, 2001)
The grapevine rootstock 420-A is the most utilized in viticulture. In order to establish a protocol of micropropagation from that rootstock, was made several experiments in vitro and glasshouse. In vitro establishment of the grapevine rootstock 420-A were carried out with nodal segments taken from shoots of hardwood cuttings stocked under cold temperature (4 / 6º C) for least period of 30 days. The shoots was sterilized by dipping in benomyl (2g.L-1) for 2 hours and NaOCL 2.5% supplemented with tween 20 (0,1%) for 20 minutes. In the initial culture, different cytokinins (BAP and kinetin) and concentrations (0/ 1/ 5 and 10 µM), different MS salts concentrations (MS/ MS/2/ MS/4 and MS/8) and different culture media (MS/ NN and WPM) were tested. During the multiplication of shoots, different culture media (MS/ MS/2/ NN and WPM) were tested. In the rooting different culture media was tested (MS/2 liquid with phenolic foam; MS/2 solid and MS/2 with addition of charcoal (1g.L-1). In the acclimatization of shoots different substracts (rices rind/ vermiculite and commercial substract Plantmax) was tested. The evaluation of the experiments was carried out through percentage shoots of the axillary bud, main shoot length, number of leaves for main shoot, number of shoots for explant and percentage of the explants lost for contamination and browning. In the rooting experiment percentage of the explants with roots and number of the roots for explant was evaluated. The kinetin did not effect the development shoots of axillary bud. BAP (1/ 5 and 10µM) increased the number of shoots (1.3/ 1.76 and 1.75 shoots/explant), respectively. The increase of BAP concentration reduced the number of leaves per explant and increased the vitrification. The best results was obtained with 1 µM BAP. The medium culture MS led to increase growth of shoots in the initial culture (24.4 mm). The growing shoots was mostly inhibited in the culture media MS/4 and MS/8, especially after their first subculture. For the multiplication of shoots the half strength MS medium seemed to be the most appropriate. Rooting occurs during multiplication of shoots, thus the use of charcoal in the medium culture is indispensable for rooting. The bigger survival of shoots was registred when were used vermiculite (95.8%) and Plantmax (87%) for the aclimatization. It was concluded that rootstock 420-Acan be micropropagated through nodal segments in culture medium MS supplemented with 1µM BAP, the multiplication of shoots in half strength MS medium and aclimatization with vermiculite and Plantmax.